A novel Ag doping Ti alloys route: Formation and antibacterial effect of the TiO2 nanotubes - Taipina, Márcia O.; de Mello, Mariana G.; Tamborlin, Leticia [UNESP]; Pereira, Karina D. [UNESP]; Luchessi, Augusto D. [UNESP]; Cremasco, Alessandra; Caram, Rubens (Elsevier, 2021)
Titanium has been widely used for clinical purposes, but post-surgical infections remain a troublesome issue, impairing patient's quality of life. Silver (Ag) is a potent broad-spectrum antimicrobial agent whose disinfecting effect has been known for centuries. In light of this fact, as an attempt to provide a long-term solution to prevent implant-associated infection, we produced Ti–35Nb alloys containing Ag, using different methods to incorporate it. These alloys were subjected to an electrochemical process to produce TiO2 nanotubes on their surface, in an attempt to further improve the material's bioactivity. Also, on the Ti–35Nb substrate, TiO2 nanotubes were grown and then decorated with Ag by UV light-induced photoreduction. The results indicate that Ag does not affect the formation of TiO2 arrays. Furthermore, the results show that added Ag can elicit antibacterial activity without leaching significant amounts of Ag that are considered toxic to mammalian cells. An initial cytotoxicity evaluation was conducted with pre-osteoblast cell line (MC3T3-E1) and its viability profile was indirectly assessed by MTT assay. Results indicate that the presence of TiO2 improves osteoblast proliferation and that Ag addition seems to mostly promote cell proliferation.
Keywords: Ag; Bactericidal effect; Biomaterial application; Cell proliferation; TiO2 nanotubes